Hereditary Thrombotic Thrombocytopenic Purpura in a Chinese Boy With a Novel Compound Heterozygous Mutation of the ADAMTS13 Gene - Dai, Yi-ling; Tang, Xue; Chen, Hong-bo; Peng, Qiu-yu; Guo, Xia; Gao, Ju (Frontiers in Pediatrics, 2020)
Hereditary thrombotic thrombocytopenic purpura (TTP) is caused by ADAMTS13 mutations with autosomal recessive inheritance. It typically presents during childhood and is frequently misdiagnosed as immune thrombocytopenia. We present a case of hereditary TTP with an undescribed compound heterozygous ADAMTS13 mutation in a Chinese boy. A 12-year-old boy with a history of intermittent thrombocytopenia in the prior 6 years had severe deficiency of plasma ADAMTS13 and harbored a novel compound heterozygous mutation which was also identified in his sister. The c.577C>T was a pathogenic variant reported exclusively in Japanese cases. The undescribed c.2397C>A non-sense mutation was predicted to encode a truncated protein. Identification of the specific novel heterozygous ADAMTS13 mutation in the Chinese family, consisting a variant restricted to Asian individuals and an undescribed c.2397C>A non-sense mutation, demonstrates genetic diversity underlying hereditary TTP, and possibly ethnic skewed mutation profiles.